Selecao de cultivares de mandioca para adaptacao ao agroecossistema e potencial de rendimento - Ternes, M. (International Center for Tropical Agriculture, 1991)
Efforts of the Empresa Catarinense de Pesquisa Agropecuaria to select cassava cv. adapted to the 3 main ecosystems of the state (south, upper Vale do Itajai, and west) are indicated. The selection process involves (1) introduction and preliminary selection (resistance to bacterioses); (2) advanced trials or adaption to the ecosystem (resistance to bacterioses, anthracnose, and pests as well as root and starch productivity, the latter of min. 26 percent); (3) regional trials (root and aerial part productivity, starch and flour production, disease resistance); (4) cv. release; and (5) multiplication of cuttings. Yield potential of cv. was found to be closely related to soil and climatic conditions; in trials carried out at 4 sites, root yields of cv. Mico and Aipim Gigante in western Santa Catarina were 36 percent higher than those obtained by the same cv. in upper Vale do Itajai. Double-cycle crops in sandy soil yielded twice as much as single- cycle crops; yields on clayey soils were almost the same for both double- and single-cycle crops. (CIAT)